Chinese mental health workers' family-focused practices: a cross-sectional survey - Hao Yao; Lili Guan; Changchun Zhang; Yang Pan; Jinxiang Han; Rui He; Zhengjiao Chang; Tianhang Zhou; Chunyu Du; Tingfang Wu; Jingwen Sun; Yilin Yuan; et al. (BMC, 2021)
Abstract Background Mental disorders impose heavy burdens on patients' families and children. It is imperative to provide family-focused services to avoid adverse effects from mental disorders on patients' families and children. However, implementing such services requires a great deal of involvement of mental health workers. This study investigated the attitudes, knowledge, skills, and practices in respect to family-focused practices (FFP) in a sample of Chinese mental health workers. Methods A cross-sectional study design was employed to examine the attitudes, knowledge, skills, and practices of a convenience sample of Chinese mental health workers in respect to FFP, using the Chinese version of the Family-Focused Mental Health Practice Questionnaire (FFMHPQ). Results In total, 515 mental health workers participated in our study, including 213 psychiatrists, 269 psychiatric nurses, and 34 allied mental health professionals (20 clinical psychologists, 9 mental health social workers, and 4 occupational therapists). Compared with psychiatric nurses, psychiatrists and allied mental health professionals provided more support for families and children of patients with mental illness and were more willing to receive further training in FFP. However, there were no significant differences on knowledge, skills, and confidence across different profession types. After adjusting for demographic and occupational variables, previous training in FFP was positively associated with mental health workers' knowledge, skills, and confidence about FFP, but not actual support to families and children. Conclusions Professional differences on FFP exist in Chinese mental health workers. Training is needed to engage psychiatrists and other allied workforce in dissemination and implementation of FFP in China.